2011
DOI: 10.1088/0004-637x/745/1/43
|View full text |Cite
|
Sign up to set email alerts
|

FROM X-RAY DIPS TO ECLIPSE: WITNESSING DISK REFORMATION IN THE RECURRENT NOVA U Sco

Abstract: The tenth recorded outburst of the recurrent eclipsing nova U Sco was observed simultaneously in X-ray, UV, and optical by XMM-Newton on days 22.9 and 34.9 after the outburst. Two full passages of the companion in front of the nova ejecta were observed, as was the reformation of the accretion disk. On day 22.9, we observed smooth eclipses in UV and optical but deep dips in the X-ray light curve that disappeared by day 34.9, yielding clean eclipses in all bands. X-ray dips can be caused by clumpy absorbing mate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(99 citation statements)
references
References 39 publications
7
91
0
1
Order By: Relevance
“…U Sco is another well observed Galactic recurrent nova with a subgiant companion. Ness et al (2012) examined an Xray eclipse during the 2010 outburst in detail and concluded that the mass accretion resumed as early as day 22.9, midway during the SSS phase. In a binary with a subgiant companion, thus, we can expect the mass accretion to resume just after an outburst.…”
Section: Absorption By Surrounding Neutral Hydrogenmentioning
confidence: 99%
“…U Sco is another well observed Galactic recurrent nova with a subgiant companion. Ness et al (2012) examined an Xray eclipse during the 2010 outburst in detail and concluded that the mass accretion resumed as early as day 22.9, midway during the SSS phase. In a binary with a subgiant companion, thus, we can expect the mass accretion to resume just after an outburst.…”
Section: Absorption By Surrounding Neutral Hydrogenmentioning
confidence: 99%
“…Drake et al 2008) and nova V2491 Cyg (starting its SSS state 36 d after the optical outburst, see e.g. Ness et al 2008) demonstrated that each Galactic nova seems to have its own peculiarities.…”
Section: Introductionmentioning
confidence: 98%
“…The U Sco 2010 outburst had an extensive follow-up both from space and ground, and from X-ray to near-infrared (NIR) wavelengths Munari et al 2010;Schaefer et al 2011;Banerjee et al 2010;Yamanaka et al 2010;Diaz et al 2010;Kafka & Williams 2010;Manousakis et al 2010;Ness et al 2012;Orio et al 2010;Osborne et al 2010). …”
Section: Introductionmentioning
confidence: 99%